(untitled) (Annals of Medical Research, 2022)
Aim: The aim is to investigate the importance of gastrointestinal system lesions in the etiology of anemia according to the results of gastroscopy and colonoscopy in patients with anemia according to age groups. With this, it is to determine the predictive factors that will provide or stimulate early diagnosis, especially in malignant diseases. Material and Method: In this study, the patients undergoing gastroscopy and colonoscopy with the diagnosis of anemia between 01 January 2013 and 01 January 2019 were evaluated retrospectively. 189 patients over 18 (93 female, 96 male) were covered. The patients were divided into two groups, namely below 65 and over 65. The final diagnosis was made according to outcomes of endoscopic biopsy. Results: The gastroscopy (n=189) showed a benign appearance in 173 patients (91.5%), a malign appearance in 9 (4.8%) and bleeding lesions in 7 (3.7%). In the colonoscopic evaluation (n=189), 132 patients (69.8%) were normal, 26 (13.8%) benign, 21 (11.1%) malign, in 10 (5.3%) of the patients no focus was detected due to bleeding. Malignant patients were evaluated according to age and gender, 4 (2.1%) women and 11 (5.8%) men were detected in the group under 65 years of age, and 5 women (2.6%) and 10 men (5.3%) in the patient group over 65 years of age. Colorectal cancer was detected in 20 (10.6%) of total 2130 (11.1 15.8%) malignant patients, making it the most frequent malignant disease. Conclusion: Gastroscopy and colonoscopy in the patients with anemia is very important with regard to establishment of etiology. The advanced age patients with anemia must be scanned for malign disorders.